Established pulmonary hypertension in rats was reversed by a combination of a HIF‐2α antagonist and a p53 agonist. (16th November 2021) - Zheng, Qiuyu; Lu, Wenju; Yan, Han; Duan, Xin; Chen, Yuqin; Zhang, Chenting; Luo, Xiaoyun; Chen, Jiyuan; Wang, Chao; Liu, Shiyun; Li, Yi; Tang, Haiyang; et al.
Abstract : Background and Purpose: Recent studies reported therapeutic effects of monotherapy with either tumour suppressor p53 (p53) agonist or hypoxia‐inducible factor 2α (HIF‐2α) antagonist for pulmonary hypertension (PH). This study investigated whether a combined treatment of p53 agonist, Nutlin3a, and HIF‐2α antagonist, PT2385, would be more effective than monotherapy, based on the cell type‐divergent regulation of p53 in pulmonary arterial smooth muscle cells (PASMC) and endothelial cells (PAEC) in patients and animals with PH. Experimental Approach: The SU5416/hypoxia‐induced PH (SuHx‐PH) rat model was used, along with cultured human PASMC and PAEC. Western blot, RT‐PCR, siRNA and immunohistochemical methods were used along with echocardiography and studies with isolated pulmonary arteries. Key Results: Hypoxia‐induced proliferation of PASMC is associated with decreased p53, whereas hypoxia‐induced PAEC apoptosis is associated with increased p53, via a HIF‐2α‐dependent mechanism. Combined treatment with Nutlin3a and PT2385 is more effective by simultaneously inhibiting the hypoxia‐induced PASMC proliferation and PAEC apoptosis, overcoming the side‐effects of monotherapy. These are (i) Nutlin3a exacerbates hypoxia‐induced PAEC apoptosis by inducing p53 in PAEC and (ii) PT2385 inhibits PAEC apoptosis because HIF‐2α is predominantly expressed in PAEC but lacks direct effects on the hypoxia‐induced PASMC proliferation. In rats, combination treatment is more effective than monotherapy in reversing established SuHx‐PH, especially in protecting pulmonary arterial vasculature, by normalizing smooth muscle thickening, protecting against endothelial damage and improving function. Conclusion and Implications: Combination treatment confers greater therapeutic efficacy against PH through a selective modulation of p53 and HIF‐2α in PASMC and PAEC.